2012
DOI: 10.1371/journal.pone.0051338
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Diagnostic Potential of IP-10 and IL-2 as Biomarkers for the Diagnosis of Active and Latent Tuberculosis in a BCG-Vaccinated Population

Abstract: BackgroundThe Mycobacterium tuberculosis (Mtb)-specific T-cell interferon gamma release assays (IGRAs) are useful in detecting Mtb infection but perform poorly at distinguishing active tuberculosis disease (ATB) and latent tuberculosis infection (LTBI). This study is aimed at evaluating additional cytokines as biomarkers besides interferon-gamma (IFN-γ) to improve the identification of ATB and LTBI.Methodology/Principal FindingsSixty-six patients with ATB, 73 household contacts (HHC) of ATB patients and 76 hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
64
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 40 publications
(61 reference statements)
7
64
1
2
Order By: Relevance
“…Notably, IP-10 alone had an AUC of 0.92 for discriminating active TB from LTBI. In contrast, both unstimulated and M. tuberculosis antigen-stimulated IP-10 in QFT-IT supernatant could not differentiate active TB from LTBI (35,36), although M. tuberculosis antigen-stimulated IP-10 might be more robust for diagnosis of LTBI in young children and in HIV-infected individuals with low CD4 T cell counts (35,37). Since current diagnostic methods, including IGRAs and antigen-specific IP-10 detection, perform well at identifying M. tuberculosis-infected from uninfected people, combining IGRAs or antigen-specific IP-10 detection with plasma IP-10 measurement might have greater utility for the diagnosis of active TB.…”
Section: Discussionmentioning
confidence: 91%
“…Notably, IP-10 alone had an AUC of 0.92 for discriminating active TB from LTBI. In contrast, both unstimulated and M. tuberculosis antigen-stimulated IP-10 in QFT-IT supernatant could not differentiate active TB from LTBI (35,36), although M. tuberculosis antigen-stimulated IP-10 might be more robust for diagnosis of LTBI in young children and in HIV-infected individuals with low CD4 T cell counts (35,37). Since current diagnostic methods, including IGRAs and antigen-specific IP-10 detection, perform well at identifying M. tuberculosis-infected from uninfected people, combining IGRAs or antigen-specific IP-10 detection with plasma IP-10 measurement might have greater utility for the diagnosis of active TB.…”
Section: Discussionmentioning
confidence: 91%
“…Wang et al reported that the IL-2/IFN-␥ ratio discriminated between active TB and LTBI with a sensitivity of 77.2% and a specificity of 87.2% (24). In addition, Frahm et al reported that the combination of IL-15 and MCP-1 identified active TB and LTBI with a sensitivity of 83% and a specificity of 88% (18).…”
Section: Discussionmentioning
confidence: 99%
“…The levels of several cytokines, including interleukin-6 (IL-6), IL-10, IL-15, chemokine (C-X-C) motif ligand (CXCL)/interferon gamma-inducible protein 10 (IP-10), and monocyte chemoattractant protein 2 (MCP-2), were significantly higher in TB patients than in healthy controls (7,11,(18)(19)(20)(21); although these finding suggest important roles for these factors in disease pathogenesis, they are not sufficient for diagnosing active as opposed to latent infections. Several studies have also suggested that biomarker combinations such as IFN-␥Ϫtumor necrosis factor alpha (TNF-␣), IFN-␥ϪIL-2, IFN-␥ϪIL-4, and IL-15ϪMCP-1 might be more sensitive than single markers (18,(22)(23)(24). However, a better biomarker to improve the sensitivity and specificity in discriminating between active TB and LTBI is still needed.…”
mentioning
confidence: 99%
“…결핵균에 감염되 면 T cell이 활성화되어 IL-2를 분비하고 IL-2 receptor를 세 포 표면에 발현한다. 이때 IL-2는 T cell의 증식을 촉진하 고 육아종 형성에 관여하며 결핵 감염에 대한 통제 및 면 역에 핵심적인 역할을 수행한다 (Kaufmann, 2001;Wang et al, 2012;Sharma et al, 2014). IL-2 receptor 중 α chain은 β, γ chain과는 다르게 soluble한 형태로 혈중으로 유리되고 혈 중 IL-2 receptor α (IL-2Rα)의 농도는 유전자의 발현 정도 에 따라 달라진다.…”
Section: 또한 세균이나 바이러스에 감염된 세포가 정상 T Cell을unclassified
“…IL-2 receptor 중 α chain은 β, γ chain과는 다르게 soluble한 형태로 혈중으로 유리되고 혈 중 IL-2 receptor α (IL-2Rα)의 농도는 유전자의 발현 정도 에 따라 달라진다. 따라서 혈중 IL-2Rα의 농도는 T cell 활성의 지표가 되기도 한다 (Rubin et al, 1985;Wang et al, 2012). 또한 결핵균이 잠복 감염된 환자에서 IL-2와 IFN-γ 를 모두 발현하는 T cell의 비율이 현성 감염 환자에 비하 여 높은 것으로 나타났다는 결과를 보고한 연구도 진행되 었다 (Casey et al, 2010;Sester et al, 2011).…”
Section: 또한 세균이나 바이러스에 감염된 세포가 정상 T Cell을unclassified